Clinical Practice Guidelines for the Management of Behavioral and Psychological Symptoms of Dementia: A Systematic Review With AGREE II - Ma, Huixuan; Lu, Xinliang; Zhou, Aihong; Wang, Fen; Zuo, Xiumei; Zhan, Minmin; Zou, Qi; Gong, Shuting; Chen, Yufei; Lyu, Jihui; Jia, Longfei; Jia, Jianping; et al. (Frontiers in Neurology, 2022)
Abstract Background: High-quality clinical practice guidelines (CPGs) are important for the effective treatment of behavioural and psychological symptoms of dementia (BPSD). However, recommendations provided by different quality guidelines may lead to varied clinical practice outcomes. Objective: To assess the quality of available CPGs for the management of BPSD and summarise the best recommendations for treating BPSD. Methods: This was a systematic review of CPGs for the management of BPSD with data obtained from electronic databases and evaluated using the Appraisal of Guidelines for Research and Evaluation II instrument, consisting of six domains: ‘Scope and purpose’, ‘Stakeholder involvement’, ‘Rigor of development’, ‘Clarity of presentation’, ‘Applicability’, and ‘Editorial independence’. The criteria for high-quality guidelines were set as: the score of high-quality guidelines in the ‘Rigor of development’ domain should be ≥60% and as well as a score of greater than 60% in at least 3 other domains. High-quality guidelines were selected for recommendation extraction, and the final recommendations were formed in combination with the latest meta-analysis and randomised clinical-trial results. Results: In term of median scores in each domain for the six included CPGs, ‘Scope and purpose’ (87.5%) scored better than all others, whereas ‘Applicability’ (46.5%) was the domain with the lowest score. Four CPGs (2015 APA, 2018 NICE, 2018 CANADA, 2020 EAN) met the criteria of high-quality guidelines and were used to extract recommendations. From these four CPGs, 9 specific recommendations related to the management of BPSD were summarised, of which 7 were related to pharmacological treatment and 2 to non-pharmacological treatment. These recommendations covered the applicability of antipsychotic drugs, medication recommendations, withdrawal times, and several suitable non-pharmacological therapies. Conclusion: The quality of CPGs for the management of BPSD requires improvement, especially for the ‘Applicability’ domain. For psychotic-like symptoms in dementia, the use of antipsychotics should be based on the individual's risk-benefit ratio, and the use of atypical antipsychotics seems to be a better choice. Non-pharmacological treatments may be suitable for emotional symptoms and sleep disorders.